ORGANIC CONTENT IN SEDIMENT AND MACROZOOBENTHOS ABUNDANCE IN COASTAL WATERS OF SERGANG BEACH AND MAROK TUA LINGGA DISTRICT RIAU ARCHIPELAGO PROVINCE - Endi Setiadi; Bintal Amin; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted in July 2015 in coastal waters of Sergang Beach and Marok Tua of Lingga District of Riau Archipelago Province. This research aimed to analyze the organic content in sediment, the type and abundance of macrozoobenthos and relationships between organic content in sediment, macrozoobenthos abundance and sediment particle. The method used in this research was survey method. Sampling macrozoobenthos was conducted by using 25 x 10 cm2 Ekman grab. Water quality parameters were still in the range of water quality criteria for marine organisms. The result showed that sediment organic content in Sergang Beach was 5.95 % and Marok Tua was 13.17%. The macrozoobenthos abundance varied from 373-644 ind/m2, diversity index (H’) was 0.62-0.93, dominance index (C) was 0.56-0.71 and uniformity index (E) was 0.07-0.011. Relationships between organic content in sediment and macrozoobenthos abundance in Sergang Beach were y = 2.433+0.0524x, R2=0.0057, r=0.075 and Marok Tua y = 3.5001-0.4205x, R2=0.5407, r=0.735. While relationships between sediment grain size and organic content in sediment were y = 5.8194+0.0368x, R2=0.0004, r=0.02 and Marok Tua y = -0.31+3.5229x, R2=0.147, r=0.383.Key Words: Organic, sediment, macrozoobenthos and abundance